First record of death-feigning behavior in common wolf snake Lycodon aulicus (Linnaeus, 1758) from Nepal - Sapkota, Abhishek; Karki, Apekshya; Sapkota, Keshab Raj; Baral, Rishi (Nepalese Journal of Zoology, 2025)
The rare anti-predator behavior of death feigning (thanatosis) is reported in common wolf snake (Lycodon aulicus) from Nepal. Herein, we report first documented behavior in L. aulicus from Pokhara, Nepal characterized by ventral exposure, immobility, and absence of mouth gaping and contributes important information to limited ethological knowledge of the species. Our observation highlights that snake rescue events offer valuable opportunities to study anti-predator strategies. Additionally, understanding and publicizing such non-aggressive defensive behaviors can enhance community awareness, promote safer human-snake interactions, and reduce unnecessary persecution of this non-venomous species in Nepal.